2020
DOI: 10.3126/bjhs.v4i3.27024
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Variation of Anterior Clinoid Process in Dry Human Skulls

Abstract: Introduction: The anatomical relationship of the Anterior Clinoid Process (ACP) with its neighboring structures in the base of the skull is complex with different variations. Thus, study of its morphology is essential in defining and directing surgery. Objective: This study aims to investigate the anatomy of the anterior clinoid process and prevalence of Caroticoclinoid foramen (CCF) to highlight its variations. Methodology: The measurements were performed in 31 dry human skulls to define the struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…Our study concurred with the study by Natsis K et al 21 but their values for the ACP-PCP distance are higher than our values and distance between ACP tips and distance between PCP tips are much lower than our values. Our study also concurred the studies by Lone M et al 7 and Dagtekin A et al 10 but their values for all the parameters in parasellar region are lower than our values (table 4) 3 Natsis K et al 5 Lone M et al 18 Dagtekin A et al A study by Neslihan B et al 22 found that distance between ACP tips was 25.8±2.7mm and the distance between ACP-PCP was 10.7±2mm in right and 10.4±2.1mm in left side and these values are higher than our values. Most of the previous studies are from outside India and few are from southern and eastern part of India but our study was conducted on the population of North India.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study concurred with the study by Natsis K et al 21 but their values for the ACP-PCP distance are higher than our values and distance between ACP tips and distance between PCP tips are much lower than our values. Our study also concurred the studies by Lone M et al 7 and Dagtekin A et al 10 but their values for all the parameters in parasellar region are lower than our values (table 4) 3 Natsis K et al 5 Lone M et al 18 Dagtekin A et al A study by Neslihan B et al 22 found that distance between ACP tips was 25.8±2.7mm and the distance between ACP-PCP was 10.7±2mm in right and 10.4±2.1mm in left side and these values are higher than our values. Most of the previous studies are from outside India and few are from southern and eastern part of India but our study was conducted on the population of North India.…”
Section: Discussionsupporting
confidence: 93%
“…The anterior clinoid process are the bony projections presents on the medial end of lesser wing of sphenoid bone and connects the body of sphenoid to the lesser wing by two roots -anterior and posterior root (optic strut) [3][4][5] . Anterior root of the anterior clinoid process forms the roof and posterior root forms the floor of the intracranial part of optic canal, whereas the base of the anterior clinoid process forms a part of lateral wall of optic canal [6][7][8] . The anterior clinoid process (ACP), optic strut (OS) and the surrounding parasellar structures are very important as they are closely related to the nerves, vessels, glands, and part of base of brain like optic nerve, ophthalmic artery, internal carotid artery, cavernous sinus, pituitary gland, basilar artery and interpeduncular fossa 9,10 .…”
Section: Introductionmentioning
confidence: 99%